2021
DOI: 10.3390/jof7040256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static Magnetic Field on Monascus ruber M7 Based on Transcriptome Analysis

Abstract: The effects of a static magnetic field (SMF) on Monascus ruber M7 (M. ruber M7) cultured on potato dextrose agar (PDA) plates under SMF treatment at different intensities (5, 10, and 30 mT) were investigated in this paper. The results revealed that, compared with the control (CK, no SMF treatment), the SMF at all tested intensities did not significantly influence the morphological characteristics of M. ruber M7, while the intracellular and extracellular Monascus pigments (MPs) and extracellular citrinin (CIT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Recently, more and more researchers are utilizing multiomics in combination with genetic, biochemical and molecular biology approaches to systematically investigate magnetobiological effects on organism growth and development. For example, three days of exposure of Monascus ruber M7 to 30 mT SMF significantly increased the accumulation of Monascus pigments and citrinin, which was consistent with the transcriptomic data showing that a number of genes involved in the pigment and citrinin biosynthesis, as well as in the primary metabolism, were upregulated by SMF [ 32 ]. In addition, moderate-intensity SMF could enhance the efficiency of a halotolerant yeast to decolorize azo dye via upregulating the expression of genes functioning in intracellular synthesis and the accumulation of glycerol [ 33 ].…”
Section: Introductionsupporting
confidence: 85%
“…Recently, more and more researchers are utilizing multiomics in combination with genetic, biochemical and molecular biology approaches to systematically investigate magnetobiological effects on organism growth and development. For example, three days of exposure of Monascus ruber M7 to 30 mT SMF significantly increased the accumulation of Monascus pigments and citrinin, which was consistent with the transcriptomic data showing that a number of genes involved in the pigment and citrinin biosynthesis, as well as in the primary metabolism, were upregulated by SMF [ 32 ]. In addition, moderate-intensity SMF could enhance the efficiency of a halotolerant yeast to decolorize azo dye via upregulating the expression of genes functioning in intracellular synthesis and the accumulation of glycerol [ 33 ].…”
Section: Introductionsupporting
confidence: 85%
“…The process through which the magnetic field affects organisms is intricate and integrated, and the effect of magnetic field intensity on the growth of Monascus also exhibits a dose–effect relationship . In contrast, a low-frequency magnetic field can increase the production of pigments and Monacolin K without affecting the normal growth of the mycelium while reducing the synthesis of CIT and downregulating the expression of associated regulatory genes. Consequently, with proper application, low-frequency magnetic fields can be potent instruments for enhancing the efficiency of fermentation processes.…”
Section: Control Of Cit Contamination In Cheese Productsmentioning
confidence: 99%
“…The bioynthesis of MPs depends on many factors, such as Monascus spp. strain, carbon source, nitrogen source, nitrogen to carbon ratio, pH value, and other nutritional and environmental factors ( Said et al, 2014 , Chen et al, 2017 , Patrovsky et al, 2019 , Yang et al, 2021 ). Many have reported that regulating the culture medium composition and conditions improves the yield of health-related metabolite in Monascus spp .…”
Section: Introductionmentioning
confidence: 99%